Steiner Triple Systems Intersecting in Pairwise Disjoint Blocks - Chee, Yeow Meng (The Electronic Journal of Combinatorics, 2004)
Two Steiner triple systems (X,A) and (X,B) are said to intersect in m pairwise disjoint blocks if |AB|=m and all blocks in AB are pairwise disjoint. For each v, we completely determine the possible values of m such that there exist two Steiner triple systems of order v intersecting in m pairwise disjoint blocks.